2019
DOI: 10.1002/clc.23174
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic modifications induced by breast implants

Abstract: Background Echocardiography realization can be challenging in the presence of breasts implants (BI). It is less known if electrocardiograms (ECG) may be modified in the presence of BI. Methods ECG from women with BI (and without any known cardiac structural disease) were sent and analyzed by two experienced electrophysiologists (EP1 and EP2) who were blinded and completely unaware of the context of the patients (Group 1). ECG from a control matched‐group of female women without BI (Group 2) were also blindly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 9 publications
0
14
2
3
Order By: Relevance
“…Since the vast majority of participants did not have preoperative ECG, the abnormalities on the ECGs could not be attributed to the BIs for certain. However, the prevalence of ECG abnormalities reported in this study was significantly higher than a study including a large population of non-athlete young female subjects, in which mainly QT abnormalities were detected [2,3]. Although the absence of R wave progression from V1 to V4 was reported in some individuals in the previous study, there is no report regarding low QRS voltage in both precordial and limb derivations in a woman with BIs.…”
Section: Copyright  Abdullah Kaplancontrasting
confidence: 88%
See 1 more Smart Citation
“…Since the vast majority of participants did not have preoperative ECG, the abnormalities on the ECGs could not be attributed to the BIs for certain. However, the prevalence of ECG abnormalities reported in this study was significantly higher than a study including a large population of non-athlete young female subjects, in which mainly QT abnormalities were detected [2,3]. Although the absence of R wave progression from V1 to V4 was reported in some individuals in the previous study, there is no report regarding low QRS voltage in both precordial and limb derivations in a woman with BIs.…”
Section: Copyright  Abdullah Kaplancontrasting
confidence: 88%
“…The low-voltage Electrocardiogram (ECG) can be associated with either the problems of voltage generated by the heart or other non-cardiac conditions such as the problems of voltage transmission and electrode placement and equipment issues [1]. In recent years, Breast Implants (BIs) in women have been shown to cause ECG modifications [2]. However, the impacts of BIs on ECG modification have not been studied thoroughly in a large-scale prospective study.…”
Section: Introductionmentioning
confidence: 99%
“…Research also has shown evidence of further inaccuracy in ECG interpretation in patients after breast augmentation with implanted silicone breast prostheses compared with unaugmented breast tissue. In a blinded study, experienced electrophysiologists analyzed the ECGs of participants with and without silicone breast implants 28. Of participants with breast implants, 42% to 46% were inaccurately interpreted as abnormal 28.…”
Section: Diagnosismentioning
confidence: 99%
“…Alternative imaging modalities are therefore commonly required to ensure accurate diagnosis and appropriate clinical decision-making. Investigation and monitoring of incident CV toxic effects also requires optimal CV noninvasive imaging, and the spectrum of disease demands a multimodality approach, with false-positive results reported in this patient group with both electrocardiography and nuclear (single-photon emission computed tomography) imaging …”
mentioning
confidence: 98%